Movement imagery as a predictor of online control in typically developing children. Issue 6 (18th August 2018) - Sooley, Marcus; Cressman, Erin K.; Martini, Rose
ABSTRACT: The ability to mentally represent actions is suggested to play a role in the online control of movement in healthy adults. Children's movement imagery ability and online control have been shown to develop at similar nonlinear rates. The current study investigated the relationship between movement imagery and online control in children by comparing implicit and explicit movement imagery measures with the ability to make online trajectory corrections. Imagery ability was a significant predictor of children's online control of movement once general reaching efficiency was controlled for. These findings extend the proposed relationship between movement imagery and online control.